Psichologija - faktor, opredeljajuscij uspech v sporte (po stranicam zarubeznoj pecati) - Ozolin, E. S. (Teorija i Praktika fiziceskoj Kul'tury, 2004)
The Article is devoted to the review of practical recommendations of the foreign sports psychologists which are the most popular among foreign athletes and coaches which publish the results of the researches rather frequently in the Internet.